Efektivitas Model Pembelajaran Discovery Learning Berbantuan Phet Simulation Untuk Meningkatkan Kemampuan Literasi Matematis Peserta Didik Pada Materi Energi Potensial Pegas - Maria F. Bay Nio; Kristiana Nathalia Wea; Maria Enjelina Suban (Departement of Mathematics Education, 2024)
An ability that plays an important role in learning mathematics and physics in the 21st century is mathematical literacy skills. This study aims to analyze the mathematical literacy ability of students using the PhET Simulation-assisted Discovery Learning learning model in Spring Potential Energy material. This type of research is pre-experimental using a one-group pretest-posttest design. The subjects of this study were 13 students of class XI MIA SMAK Santa Maria Monte Carmelo Maumere. Students before learning are given an initial test and at the end of learning are given a final test with the same material and form of questions. The pretest and posttest result data were then analyzed using validity tests, reliability tests, normality tests, homogeneity tests, paired t-tests, and n-gain calculations with IBM SPSS Statistics 26. This study showed a significant increase in scores after being given physics learning using the Discovery Learning learning model. The Discovery Learning learning model assisted by PhET Simulation is effective in improving students' mathematical literacy skills. This is evidenced by the significant value gains on paired t-tests and n-gain tests are 0.023 and 0.8531 respectively. With this, the Discovery Learning learning model assisted by PhET Simulation can be used as a reference or consideration for teachers to improve students' mathematical literacy skills.